Short-term Resistance Training Increases APPL1 Content in the Liver and the Insulin Sensitivity of Mice Fed a Long-term High-fat Diet - Minuzzi, Luciele Guerra; Kuga, Gabriel Keine [UNESP]; Breda, Leonardo; Gaspar, Rafael Calais; Muñoz, Vitor Rosetto; Pereira, Rodrigo Martins; Botezelli, José Diego; Da Silva, Adelino S. R.; Cintra, Dennys Esper; De Moura, Leandro Pereira; Ropelle, Eduardo Rochete; Pauli, José Rodrigo (Thieme, 2020)
Background APPL1, an adapter protein, interact directly with adiponectin receptors mediating adiponectin signaling and acting as a critical regulator of the crosstalk between adiponectin and insulin signaling pathway. The inadequate level of physical activity, high-calorie intake, or both lead to adverse consequences on health, like insulin resistance. On the order hand, physical exercise acts positively in the insulin action. Purpose Here, we investigated the effects of short-term resistance training (RT) on APPL1 content and adiponectin pathway in the liver of mice fed a long-term high-fat diet. Methods Swiss mice were distributed into 3 groups: Mice that fed a chow diet (CTR); Mice fed a high-fat diet for 16 months (HFD); and mice fed a high-fat diet for 16 months and submitted to a climbing ladder exercise (RT) for 7 days (HFD-EXE). Results The results show that short-term RT increases the APPL1 content but wasn't able to alter AdipoR1 and AdipoR2 content in the liver of HFD-EXE mice. However, this increase in the APPL1 content in response to RT was accompanied by improvement in the insulin sensitivity. Conclusion In summary, our data suggested that short-term RT improves glycemic homeostasis and increases APPL1 in the hepatic tissue of mice treated with long-term high-fat diet.
Keywords: adiponectin; APPL1; hepatic tissue; obesity, elderly; resistance training